J.J. Viljoen and T.K. Kamupingene. Otjiherero woordeboek dictionary embo romambo. - Kavari, Jekura U. (Lexikos, 1994)
Review of J.J. Viljoen and T.K. Kamupingene. Otjiherero woordeboek dictionary embo romambo.